PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN DI SEKOLAH YAYASAN PEMBINAAN ANAK CACAT (YPAC) PALEMBANG - Putra, Ignatius; Wibagso, Stefanus Setyo; Triayomi, Ria; Sukarman, Sukarman; Jamilah, Masayu (Universitas katolik Musi Charitas, 2021)
Learning media is an important part of learning facilities and infrastructure in schools to help students not only learn abstractly but also concretely. According to Faizal (2010), learning media as audio and visual instruments are used to help the learning process become more interesting and arouse students' interest in exploring a material. However, in reality it is often found in schools that learning media is very limited and not many teachers are interested and creative in making learning media. They are many reasons such as limited funds, time, knowledge, and the reluctance of teachers to make learning media. Therefore it is necessary to equip teachers in making easy and cheap ICT-based learning media. This training was given to teachers at the YPAC school in Palembang who were in great need. The targets and outputs of this activity are to produce simple learning media for children with special needs and to train teachers' creativity in making and using these learning media. The basic training by a team of lecturers at the SI and PGSD Study Program at Musi Charitas Catholic University is the first step to stimulate interest and collaboration between teachers to be more creative in making simple ICT-based learning media as well as expanding teacher knowledge. The training is provided in the form of basic training in making simple learning media for children with special needs and how to use them in learning. The methods used are lectures, questions and answers, demonstrations, and experiments. Hopefully, all participants have sufficient skills to create learning media according to student characteristics.